PENYUSUNAN MODUL PEMBELAJARAN BERBASIS SAINS TEKNOLOGI DAN MASYARAKAT (STM) PADA KONSEP BIOTEKNOLOGI (Sebagai Bahan Ajar Siswa SMA Kelas XII) - Desi Eka Nur Fitriani; Evi Amelia; Pipit Marianingsih (Universitas Negeri Jakarta, 2017)
This research aimed to develop a learning module on biotechnology based on Sains Technology Society (STM) and to know the module quality according to the expert assessments. This research was a developments research (R & D) with 3-D (Define, Design, and Develop) model. The instruments in this research were questionaire and expert assessment sheets. Module was assessed from the feasibility aspects of content, sains technology society (STM), language, presentation and layout. The data from questionaires and assessment sheets was used to improve the module contents and structures. The result of this research was a learning module based on the sains technology society (STM) on biotechnology. The result assessment according to the expert showed that the modul was 93,8% with category very good and feasible to use as learning module for 12th grade of senior high school.